Degradação da matéria orgânica proveniente de efluente de indústria de madeira, empregando fotocatálise e radiação solar - Souza, Danilo Rodrigues de (2004)
In the present work, the thennal Fenton and photo - Fenton reactions were used in order to perform the degradation of the organic matter present in wastewater provenient of SATIPEL S/À, a plywood industry located in Uberaba - MG. The effect of differcnt parameters (pH, temperature, iron(II) sulphate concentration, and hydrogen peroxide concentration) vvas evaluated in relation to the apparent rate constant for the degradation of the organic matter. The results showed tliat the best pH to perform these reactions ranges from 2.8 to 3.0. A temperature survey showed that its increase favours the reaction rate. B es ides, it was possible to estimate the energy of the activation in around 20,8 kJ/mol (± 7,6 kJ/mol), a relatively low value, which indicates a radical-mediated process. Essays made using iron (II) sulphate showed that the concentration range that was studied did not influence significantly the reaction rate. It vvas also observed a positive effect in the degradation result related to the hydrogen peroxide concentration. Essays using solar radiation and CPC reactors (in small and large scale), the use of the reactor allowed evaluating the degradation of the organic matter in volumes up to 50 L. An organic matter degradation up to 90% was achieved with a UV-A dose of 1,000 kJ/m2, when a mixture of iron (II and III) sulphate (50% w/w) was used, attributed to the synergistic effect between both species. When potassium iron (III) oxalate was used, a degradation up 92% was achieved, with an UV-A dose near 400 kJ/m2. HPLC essays confirmed the mineralization of the organic matter. The reduction of peaks was convincing enough and the reduction of the total area chromatogram was 55 % for an accumulated UV-A dose around 965 kJ/m2